Managing air quality in Santiago: what needs to be done? - O´Ryan, Raúl; Del Valle, Alfredo (Estudios de Economía, 2016)
This paper presents the bases for the design of a systemic management system for air quality in Santiago. The system proposed was developed through a novel participative methodology called Innovative Development, that required the participation of all the actors of the systems. As a result, an action map that provides systematic and action oriented view of what needs to be done to effectively manage Santiago’s air quality at a general level has been developed. This map –constituted by 16 basic and 92 specific lines of action- distinguishes between established lines i.e., lines that the actors considered sufficiently managed, and non-established lines, where management, from an air quality perspective, is insufficient or non-existing. The basic messages delivered by the action map are that the established lines correspond chiefly to the system building effort undertaken between 1990 ans1994 focused on controlling “easily reducible” emissions, and improving the monitoring capacities.